The Cultural Evolution of Mobile Phone Use: A Catalyst for Information Access and Socialisation among Students in Nigerian universities - Ayodele, Kolawole Samuel; Oni, Oluwafemi Omotade (POMLIF Journal of Library and Information Science, 2021)
The study examined the cultural evolution of mobile phone as a catalyst for information access and socialisation among Nigerian students. The study used integrative analysis of literature to review the findings in related researches with the view to drawing an inference. The study observed that mobile phone revolution has changed students behaviourally in many sphere of lives. This means students have become addicted to mobile phone use, it had made them imbibed some attitudes which were hitherto alien to them. The study found that mobile phone culture amongst students is responsible for changes of attitudes such as easy access to information, reduction in cognitive ability, cheating in various forms, poor writing skills, activities associated to risk of lives and so on. The study recommends that authorities of higher institutions should endeavour to organize summits on the danger of phone addition amongst students with a view to reducing the catastrophic effects of mobile phone culture on socialization of students. Benefits of accessing needed information by way of sharing and accessing lecture materials online, easy communication with colleagues and course master through the use of mobile phone device should be further encouraged by the school authorities at all levels.